2011
DOI: 10.1186/1743-422x-8-478
|View full text |Cite
|
Sign up to set email alerts
|

Emerging trends in Lassa fever: redefining the role of immunoglobulin M and inflammation in diagnosing acute infection

Abstract: BackgroundLassa fever (LF) is a devastating hemorrhagic viral disease that is endemic to West Africa and responsible for thousands of human deaths each year. Analysis of humoral immune responses (IgM and IgG) by antibody-capture ELISA (Ab-capture ELISA) and Lassa virus (LASV) viremia by antigen-capture ELISA (Ag-capture ELISA) in suspected patients admitted to the Kenema Government Hospital (KGH) Lassa Fever Ward (LFW) in Sierra Leone over the past five years is reshaping our understanding of acute LF.ResultsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
94
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 27 publications
5
94
2
2
Order By: Relevance
“…Increased levels of antigenemia have been found in fatal cases of Lassa fever compared with those in nonfatal cases (50). The short duration of antigenemia makes the detection of Lassa virus antigen more specific to acute Lassa virus infection than detection with antibody assays.…”
Section: Antigen and Antibody Detection Assaysmentioning
confidence: 89%
See 3 more Smart Citations
“…Increased levels of antigenemia have been found in fatal cases of Lassa fever compared with those in nonfatal cases (50). The short duration of antigenemia makes the detection of Lassa virus antigen more specific to acute Lassa virus infection than detection with antibody assays.…”
Section: Antigen and Antibody Detection Assaysmentioning
confidence: 89%
“…Antibody assays have been used to diagnose Lassa fever in those with a clinically consistent illness based on either detectable levels of Lassa virus antibody in a serum sample collected during illness or a rise in Lassa antibody titers (2,63). However, Lassa virus IgM titers remain elevated for months to years following an acute infection (50). One study found that 28% of healthy hosts sampled from a region where the virus is endemic without a recent preceding febrile illness had detectable levels of Lassa virus IgM, suggesting that IgM positivity alone may be insufficient to diagnose Lassa fever in persons residing in regions where it is endemic (50).…”
Section: Antigen and Antibody Detection Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6] The Kenema District of Sierra Leone is a Lassa-endemic region, although it is currently unknown what the burden of Lassa fever is in relation to other febrile illnesses in the region. In addition, there are no studies to date that broadly examine the etiologies and outcomes of febrile illness in patients seeking healthcare in Sierra Leone.…”
Section: Introductionmentioning
confidence: 99%